Java programmer's reference - Palmer, Grant (Programmer to programmer, 2000)
Covers the 12 most commonly used packages of Java 2 SDK, version 1.3: Java language, utility, I/O, network programming classes, and GUI development using the Abstract Windowing Toolkit and Swing, applets, event handling, and Java Beans.